Orexin system and pathogenesis of sleep-wake cycle disturbances in narcolepsy - Yu. V. Gavrilov; K. Z. Derevtsova; H. A. Korneva (Бюллетень сибирской медицины)
Sleep is the one of the most important vital functions of the body. The study of the primary mechanisms that result in disturbance of the sleep-wake cycle is a priority of modern medical science. It is known that the orexin neurons of the hypothalamus, which send projections to all waking centers, play a leading role in initiating and maintaining this state. Insufficiency of the function of the orexinergic system of the hypothalamus leads to disturbances in the sleep-wake cycle and the development of the severe diseases of narcolepsy and cataplexy. The presented review is devoted to the investigation of possible mechanisms of development of pathological changes in the orexin-containing neurons functions and the diseases caused by them.